Mechanical properties of macáçar beans (Vigna unguiculata) at different moisture content (Research, Society and Development, 2020)
The macáçar bean is a crop used in food, being of great economic and social importance, because present high nutritional value. With the expansion of large-scale macáçar bean production it is necessary to improve machines in order to avoid insults in the integument due to mechanical damages at harvest time. Thus, the objective of this work was to evaluate the mechanical properties of bean pods as a function of the different moisture contents obtained with drying. Manatee beans harvested manually, with an initial moisture content of 2.38 (decimal b.s.) in the municipality of Santa Helena de Goiás (GO). The moisture contents (0.73, 0.71, 0.66, 0.50, 0.38, 0.35, 0.18, 0.11, 0.05, decimal bs) were obtained by drying furnace with forced ventilation, maintained at a temperature of 50 ºC. The samples were submitted to uniaxial compression in natural resting position in the texturometer equipment. According to the results obtained, it is concluded that the moisture content influences the mechanical properties of the macáçar beans. As the moisture content decreases, it reduces the absorbed energy and the breaking force and the proportional modulus of deformity increase. The reducing the moisture content provides the grains with greater impact resistance during product preprocessing.